Islamic Republic of Mauritania : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Islamic Republic of Mauritania. (IMF Staff Country Reports; Country Report ;, 2020)
This paper focuses on the Islamic Republic of Mauritania's Request for Disbursement Under the Rapid Credit Facility. The economic and social impact of the pandemic is rapidly unfolding, with a contraction of output expected in 2020. The authorities have responded swiftly with measures to contain the pandemic and alleviate its fallout. Going forward, prioritizing health spending and targeted support to the most vulnerable households and sectors in the economy remains critical. The authorities are committed to full transparency and reporting of resources deployed for the emergency response, to audit crisis-mitigation spending once the crisis abates, and to publish the results. At the same time, they remain committed to the economic reform program supported by the ongoing ECF arrangement with the IMF. The program aims at using the fiscal space to increase priority spending on education, health and social protection and infrastructure, while mobilizing domestic revenues and maintaining prudent borrowing policies to preserve debt sustainability.